General self‐efficacy and social support as mediators of the association between perceived stress and quality of life among rural women with previous gestational diabetes mellitus. Issue 7 (25th January 2021) - Long, Qing; Guo, Jia; Zhong, Qinyi; Jiang, Shan; Wiley, James; Chen, Jyu‐Lin
Abstract: To explore the association between perceived stress and quality of life (QoL) and the mediating role of general self‐efficacy and social support in this association. Gestational diabetes mellitus (GDM) is one of the most common metabolic diseases suffered by pregnant women. Women with previous GDM may experience more medical‐related stress and have a lower QoL than those without it. A multisite correlational study. Four hundred sixty‐five women with previous GDM living in rural areas in China participated in this study from November 2017 to June 2019. The participants completed a set of self‐reported socio‐demographic questionnaires, the Perceived Stress Scale, the General Self‐Efficacy Scale, the Social Support Rating Scale and the World Health Organization QoL assessment (Brief version). STROBE checklist was used as the guideline for this study. The mean QoL score was 13.97 (SD 2.07) for physical health, 13.75 (SD 1.98) for psychological health, 14.96 (SD 1.99) for social relations and 12.49 (SD 1.74) for environmental conditions. About 43.9% of women with previous GDM reported increased stress, which was negatively correlated with each of these QoL domains. Yet, the negative effect of perceived stress on QoL could be completely or partly mediated by better social support or general self‐efficacy among this population. Nearly half of the women in the study living in rural China reported increased stress after delivery, and there is room to improve QoL in the environmental domain among women with previous GDM. Increasing general self‐efficacy or social support can help these women avoid the negative effects of perceived stress on their QoL. These findings suggest that healthcare providers need to be cognizant of the importance of self‐efficacy and social support for women with previous GDM in both enhancing QoL and reducing the negative impact of perceived stress on QoL.